Analisis Hukum Ancaman Krisis Iklim Terhadap Pulau Kecil Terluar dan Implikasinya terhadap Pertahanan dan Keamanan Nasional Indonesia - Parluhutan Sagala; Muhammad Jamil; Ilman Hadi; Arief Fahmi Lubis (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Climate change, especially the threat to the outermost small islands, has a significant impact on Indonesia's national resilience. The worsening climate crisis has the potential to threaten the survival of coastal communities, trigger tensions in border areas, and worsen the social and economic situation through mass migration. This study aims to analyze the threat of the climate crisis to the outermost small islands and its implications for Indonesia's national defense and security. The method used is a normative legal analysis with a statutory, conceptual, and case approach, with deductive reasoning. The findings show that Indonesia, as the largest archipelagic country, faces real threats due to climate change, such as rising sea levels that can submerge many outermost small islands. This threat has the potential to affect territorial sovereignty, economic stability, and food security, and can trigger social and international conflicts. This study also identifies the need for mitigation policies, including the New and Renewable Energy Bill, and the Climate Change Management Bill, to reduce greenhouse gas emissions and strengthen the country's resilience to the impacts of climate change.